Three in one: triple G-C-T base-coded brahma nucleobase amino acid: synthesis, peptide formation, and structural features - Wagh, Mahendra A.; Maity, Rahul; Bhosale, Rohit J.; Semwal, Divyam; Tothadi, Srinu; Vaidhyanathan, Ramanathan; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2021)
This note reports the synthesis and peptide formation of a novel triple G-C-T nucleobase amino acid (NBA) building block featuring three recognition faces: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Readily obtainable in multigram scale in a remarkably easy one-step reaction, this unique NBA building block offers scope for wide ranging applications for nucleic acid recognition and nucleic acid peptide/protein interaction studies.